Yona of the dawn. 41 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2024)
"Yona and friends embark on a dangerous mission to get Meinyan back--by sneaking into an enemy camp where the Dromos assassins await! Val must battle his former South Kai comrade General Hittan for Meinyan's sake, but the rescue effort backfires once the cruel Emperor Chagol draws near!"--Back cover.